Reduction without Reductionism: Re-Imagining Religious Studies and Religious Education - Lewin, David (Implicit religion, 2020)
School and university teachers of Religious Studies (RS) are caught between presenting the irreducible complexity of their subject matter, and the practicalities of selection and simplification that pedagogy entails. The entanglements of culture, politics and ideology within RS, along with the colonialist and hegemonic histories of the subject, make questions of just representation especially acute. How can educators be inclusive and selective? The central strand of my argument concerns the “translation” between the academic study of religion in universities and religious education in schools. I argue that this translation necessarily involves “pedagogical reduction” - the selections and simplifications that teaching involves - and that we must carefully consider the basis upon which we form our pedagogical reductions. Establishing that basis depends on interdisciplinary dialogue between scholars of religion, scholars of education, and educators more generally. I argue that there is a conspicuous disconnection between critical scholarship in the scientific study of religion(s) and critical scholarship in the “educational sciences.” I justify the need for, and outline the nature of, dialogue between these scholarly communities through consideration of four interrelated pedagogical concepts that I offer as preliminary outlines towards the development of more robust and systematic criteria for developing a religious education that is simultaneously inclusive and selective.